Performance of heat-damaged partially-insulated RC beams strengthened with NSM CFRP strips and epoxy adhesive. (20th January 2018) - Jadooe, Awad; Al-Mahaidi, Riadh; Abdouka, Kamiran
Highlights: The furnace temperature-time curves followed the ISO 834. We investigate an experimental and numerical study of heated RC beams. The heated beams repair with epoxy adhesive. We study the flexural behaviour with and without insulation. The models apply to RC beams after exposure to elevated temperatures. Abstract: This paper describes an experimental and numerical study of the behaviour of RC beams damaged by heating and subsequently strengthened using NSM CFRP laminates. In the experiments, two beams were normal temperature controls, and the other beams were heated under the ISO-834 standard fire curve. The flexural behaviour was studied after exposure to 700 °C and 800 °C with and without insulation on the top surface of the concrete. The parameters studied in this investigation were unheated and heat-damaged beams, level of heat exposure and use of insulation. Three beams were un-strengthened fire-damaged control beams and the other beams were strengthened with CFRP laminates after being heated. Although the ultimate load and stiffness decreased, repair with NSM CFRP laminates using epoxy adhesive was found to increase the load capacity and stiffness of the beams. Finite element models (FEMs) were able to predict the experimental behaviour reasonably well.